If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2n + 5) = 9(3n + 7) + 8 Reorder the terms: 3(5 + 2n) = 9(3n + 7) + 8 (5 * 3 + 2n * 3) = 9(3n + 7) + 8 (15 + 6n) = 9(3n + 7) + 8 Reorder the terms: 15 + 6n = 9(7 + 3n) + 8 15 + 6n = (7 * 9 + 3n * 9) + 8 15 + 6n = (63 + 27n) + 8 Reorder the terms: 15 + 6n = 63 + 8 + 27n Combine like terms: 63 + 8 = 71 15 + 6n = 71 + 27n Solving 15 + 6n = 71 + 27n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-27n' to each side of the equation. 15 + 6n + -27n = 71 + 27n + -27n Combine like terms: 6n + -27n = -21n 15 + -21n = 71 + 27n + -27n Combine like terms: 27n + -27n = 0 15 + -21n = 71 + 0 15 + -21n = 71 Add '-15' to each side of the equation. 15 + -15 + -21n = 71 + -15 Combine like terms: 15 + -15 = 0 0 + -21n = 71 + -15 -21n = 71 + -15 Combine like terms: 71 + -15 = 56 -21n = 56 Divide each side by '-21'. n = -2.666666667 Simplifying n = -2.666666667
| l+l+0.25l=135 | | -1.3g+1.9=11.1 | | 6(3s+7)=276 | | 3(2t+-1)+2t=6-t | | 6(5m+3)=3(3m+5) | | fu*7+76=12y+9087 | | p-3=114 | | 5x-2-(-3x+4)= | | 6r-9=7+4r | | 5x+7-3(2x+9)=2(x-8)-13 | | 2m+1*5= | | 4(2x+4)-20=12 | | 2(a-8)=10 | | r-ll/3=-7 | | -3(5t-4)+5t=7t-7 | | 2w+4-(3w+6)= | | -75=3g | | 20=-5/3z | | 3p*1/3=114 | | (u-10)*6=48 | | 3*1/3p=114 | | x*log(x)=600000000 | | -2.4n-3+(7.8n+2)= | | Y=-1/2x-12 | | -.5(8x-6)=6x-7 | | 10+6+3x=7*3.5 | | -2m(1+4m)5=-13 | | 2(2l-3+l)=36 | | -(3/x)=0 | | 13/6-1/2 | | 10+4+3x=7*3.5 | | 24.5=2.5-4c |